Cationic nucleopeptides as novel non-covalent carriers for the delivery of peptide nucleic acid (PNA) and RNA oligomers. Issue 9 (15th May 2018) - Tomassi, Stefano; Ieranò, Caterina; Mercurio, Maria Emilia; Nigro, Ersilia; Daniele, Aurora; Russo, Rosita; Chambery, Angela; Baglivo, Ilaria; Pedone, Paolo Vincenzo; Rea, Giuseppina; Napolitano, Maria; Scala, Stefania; et al.
Graphical abstract: Abstract: Cationic nucleopeptides belong to a family of synthetic oligomers composed by amino acids and nucleobases. Their capability to recognize nucleic acid targets and to cross cellular membranes provided the basis for considering them as novel non-covalent delivery agents for nucleic acid pharmaceuticals. Herein, starting from a 12-mer nucleopeptide model, the number of cationic residues was modulated in order to obtain new nucleopeptides endowed with high solubility in acqueous medium, acceptable bio-stability, low cytotoxicity and good capability to bind nucleic acid. Two candidates were selected to further investigate their potential as nucleic acid carriers, showing higher efficiency to deliver PNA in comparison with RNA. Noteworthy, this study encourages the development of nucleopeptides as new carriers to extend the known strategies for those nucleic acid analogues, especially PNA, that still remain difficult to drive into the cells.